Challenges in Utilization of Potential Groundwater and the Hypotheses of River for Jaffna for Cultivating Productive Water - Nirojan, K.; Subramaniam, D.; Sivakumar, S. (International Journal of Scientific and Engineering Research, 2016)
Problems of drinking water in the Jaffna is an upcoming problem which mostly depended with increasing the population, growing the cultivation activities, opening the sewage in uncontrollable manner and etc. People of the Jaffna area depend on the ground water for all the activities using open well or tube-well. For all activities, the people extract water from underground, induced the badly behaved of quality of water fluctuating the years and also which case usually not related to one, this related with all people in the Jaffna area. The knowledge area covers the potential effects of the ground water in the Jaffna area and improve the problems and effort to bargain the solution for approaching problems using the collected knowledge and information from four of the previous work done by others are reviewed in this articles. The following five articles are mainly reviewed with other literatures referred. "Groundwater potential in the Jaffna Peninsula and impacts of climate change", "River for Jaffna-cultivating productive water from salt water Lagoons in Northern Srilanka-What the water balance of Elephant Pass lagoon demonstrates", "Water problems in the Jaffna peninsula", "Jaffna peninsula water resources challenges" and," assessment of groundwater resources in Jaffna limestone aquifer”.
Keywords: Ground water Potential; Salinity